Meningkatkan Berpikir Kritis, Motivasi Belajar Menggunakan Model PBL, Talking Stick, Metode Demonstrasi - Eliza Nurliyanti; Dessy Dwitalia Sari (CV. ITTC INDONESIA, 2024)
The problem in this research is the low critical thinking skills and students' learning motivation. This is due to one-way learning, lack of use of learning models and media, and students' lack of understanding of the learning material. To overcome this problem, a combination of PBL, Talking Stick and Demonstration Methods is used. This research aims to analyze the critical thinking skills and learning motivation of fifth grade students at SDN Kelayan Selatan 6 Banjarmasin on science learning content. This research used the Classroom Action Research method, which involved fifth semester class students at SDN Kelayan Selatan 6 Banjarmasin in 2023/2024, with a total of 12 students. The research results showed that critical thinking skills at the first meeting reached a percentage of 25%, at the second meeting 50%, at the third meeting 67%, and at the fourth meeting reached 83% in the highly skilled category. In learning motivation, the first meeting obtained a score of 33%, the second meeting 58%, the third meeting 67%, and the fourth meeting achieved 100% in the very high category. It can be concluded that students' critical thinking skills and learning motivation in science learning using the PBL, Talking Stick and Demonstration Method learning models at SDN Kelayan Selatan 6 Banjarmasin are stated to have increased